Analisis Yuridis Kepastian Hukum Eksekusi Putusan Mahkamah Agung No. 109/Pk/Pdt/2022 dalam Kasus Dago Elos Ditinjau Berdasarkan UU No. 5 Tahun 1960 tentang Peraturan Dasar Pokok-Pokok Agraria - Vidi Siami Mulyanti; Nia Kurniati; Artaji Artaji (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Agrarian disputes in Indonesia often face challenges in ensuring legal certainly, including the execution of Supreme Court Decision No. 109/PK/Pdt/2022 concerning the Dago Elos land dispute. This study aims to analyze the legal certainly of the execution involving the Muller family’s claim based on the colonial Eigendom Verponding system and the physical control of the land by local communities. Using a normative judicial approach and descriptive qualitative analysis, primary legal documents and legal literature were purposively selected as the main data sources. The study found significant barriers to execution due to local community resistance and conflicts between colonial and national agrarian systems. The main conclusion highlights challenges in implementing the principle of legal certainty, even though the old rights have been recognized. The novelty of this research lies in its analysis of the relationship between colonial and national regulations in agrarian disputes. This study recommends comprehensive agrarian law reform to prevent similar conflicts and strengthen public trust in the national legal system.